Mejoramiento del contenido Cultural-Social a través de segmentos televisivos en el medio de comunicación Elite 45. - Calahorrano Quishpe, Erika Tamara (2018)
At present time, the means of communication such as television has opted for the production of content with entertainment classification, this due to the new technological age and the ease of plataforms, causing a deficit of television audience, however, in The Organic Law of Communication in Ecuador establishes articles focused on the presentation of national production, for this reason the research developed below is based on the collection of qualitative characteristics through an extensive analysis of the programming grid instituted by Elite channel 45, in addition to providing an improvement in the cultural-social content by executing in through segments in the ,media already established. Finally, on the basis of the general analysis and the study of qualitative characteristics through the review of cultural content in the grid established by the media and before changes in analogue media, the forced submission of programming quality is considered, generate with dynamism, novelty and innovation that the media must possess by addressing their audience, thus achieving a new cultural attachment that protects our roots.